Transformation of English-Based Kitab Kuning Learning Methods Through the Integration of Pesantren Tradition and the Modernization of Instruction in Islamic Boarding Schools - Maftuhah, Maftuhah; Bastami, Bastami; Heriadi, Heriadi; Tuaini, Tuaini; Surindi, Surindi; Rahman, Munawwirur; Khozin, Khozin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to explore the transformation of English-based Kitab Kuning learning methods through the integration of pesantren traditions and the modernization of instruction in Islamic boarding schools. Employing a qualitative approach with a case study design, this research was conducted at an Islamic boarding school that actively implements both traditional and modern educational practices. Data were collected through in-depth interviews, participant observation, and document analysis to obtain comprehensive and credible findings. The results reveal that the transformation process is carried out through several strategic steps, including the integration of traditional pesantren values with modern pedagogical approaches, the development of an adaptive and integrated curriculum, and the enhancement of teachers’ competencies in both religious and English language instruction. In addition, the use of English as a medium of instruction in Kitab Kuning learning encourages students to access broader Islamic intellectual resources at the global level. This transformation has a significant impact on students’ cognitive, linguistic, and cultural competencies. It not only strengthens their understanding of classical Islamic texts but also improves their English proficiency and intercultural awareness. Furthermore, this approach prepares students to actively participate in global Islamic discourse and da’wah in the contemporary era.